Eficácia da criação da APA e da Floresta Nacional do Araripe na dinâmica de perda e fragmentação da cobertura vegetal no interior e entorno das unidades de conservação - Gomes, Francisco Vladimir Silva (2022)
The degradation of the Brazilian forests has occurred differently in each biome. The Caatinga, for example, has already lost half of its vegetation cover, while the Atlantic Forest has lost about 90% and the Amazon 20%. Within the Caatinga, the Chapada do Araripe appears as an area recognized as being of high importance for conservation, either because of the high diversity of its landscapes, with humid forests, savannas and caatinga, or because of the presence of endemic species, or because of its importance as a water source that supplies urban centers downstream. To protect this area, two Conservation Units (UCs) of sustainable use were created: the APA of the Chapada do Araripe (created in 2000) and the Araripe-Apodi National Forest (created in 1945). In this work we evaluate how effective these two UCs are in protecting the area's vegetation cover. To do so, we analyzed MAPBIOMAS 6 images (1985-2020) using Fragstats software to evaluate the dynamics of deforestation, regeneration and fragmentation in the APA and FLONA and their surroundings since 1990, a decade before the APA was created. In the first 10 years, the region was losing an average of 0.45% of savanna vegetation per year, totaling 5.4% of anthropized area at the end of the period. Immediately after the implementation of the conservation unit in mid-2000, there was a considerable drop in the rate of anthropization, losing 0.09% of its area per year. This lasted until 2010, when again the indices began to grow. In 2019, the last year of monitoring, the savanna vegetation covered only 57% of the area, a reduction of 11.3% of the original cover of the APA. The NP (Number of Fragments) values found for the Araripe APA suggest that the PA went through an intense fragmentation phase in the period 2000 - 2005, especially in the savanna vegetation. There was a mild decline in fragmentation until mid-2010, when the process regained strength and remained high until the last year of analysis. We inferred that the Araripe APA, a PA category with few legal restrictions on land use, has failed to effectively protect vegetation cover and hence local biodiversity, maintaining connectivity around 80% in the savanna formation using conservative metrics. The FLONA, on the other hand, a PA of the same sustainable use group, remained with constant vegetation cover, with 99.99% of native vegetation area.